A new approach to learning Science under STEM: Peer Project Learning - Youngjin Seo; Florencio Pinela (Revista Tecnológica)
Peer Project Learning (PPL) is an interactive student-centered curriculum, which can be easily adopted by any instructors who want to change their roles from delivering information to managing a complete set of instructions. PPL is designed to meet the goals of STEM, and consists of Peer Learning in the classroom and Project Learning in the lab. In PPL, students take an active role to build up their scientific knowledge through the pre-class reading, conceptual questions in Peer Instruction, team problem solving, development and presentation of project.